Modeling of the Submersible Plate System to Counteract Erosion in the Huallaga River, Case: Yurimaguas—Loreto - Giron, Amanda (2024)
At present, the lack of optimal riparian defense systems in the Peruvian Amazonian rivers has allowed the occurrence of natural disasters. The main objective of this report is to model different alternatives of plate batteries and simulate in Iber with flow rates and bathymetry of the area to find the most optimal alternative. The HEC-HMS software was also used to obtain the maximum flood flows for return periods of 25, 50, 100, 100, 200 and 500 years for use in IBER, which allows hydrodynamic simulations of rivers and watercourses, calculating floods and delimiting zones. The simulations were performed with the 200-year return flow, 21,749.6 m3/s. For this research 3 simulations were performed, which were divided into 3 different distributions of plate batteries, these in turn were divided into 2 different angles of attack. As the most relevant results, according to the distributions of water velocity, bottom stress, specific flow and erosion along the channel, and considering that the maximum values are far from the margin to be protected, the alternative distributions of the battery of plates that gave the best results in the channel were alternatives 1 and 3. Finally, it is concluded that the most optimal alternative and angle of attack is alternative 1 and the angle of 20°, thus counteracting erosion. Therefore, with the support of ANSYS software, the same conclusion was reached as for alternative 1, but with an angle of 25°, so that the optimal angles are 20–25 degrees.